THE ROMANIAN TOURISM THROUGH THE TRAVEL AGENCIES IN PERIOD 2012-2017 - RABONTU, Cecilia Irina D. (Revista de turism - studii și cercetări în turism, 2018)
Travel agencies carry out complex activities such as organizing tourism programs and actions that they sell further to either intermediate sales agents or end-users. Representing an important segment of the tourist market, namely tourist offer, travel agencies, whether they are tour operators or with sales activity, are clearly delineated in the tourism activity through the volume and structure of the touristic activities carried out. The evolution of tourism activities supported by tourism agencies lately has attracted my interest because it can once again argue, along with other aspects related to the positive evolution of Romanian tourism. Tourism is considered to be an area of activity that can make a significant contribution to the development of any economy and especially those economies in countries with significant tourism resources with the prerequisites for sustainable tourism development, as is Romania. In this paper I will present the concerns of the specialists in this field, highlighting the most important aspects found in the specialized literature on this topic and to carry out an analysis of the official statistical data referring to incoming activity, domestic tourism activity, outgoing activity, number of Romanian tourists taking part in domestic tourism activities.